Correlates and predictors of impulsivity in adults with methamphetamine use disorder. (4th July 2019) - Lanesman, Tali H.; Gouse, Hetta; Bantjes, Jason; Stein, Dan J.; Lochner, Christine
ABSTRACT: Impulsivity is known to increase the likelihood of using stimulant drugs which in turn may increase impulsivity, leading to potentially hazardous use. However, little research has been conducted on impulsivity in methamphetamine (MA) users. In this case-control cross-sectional study, 54 adults with MA use disorder (MUD) were compared to 52 matched healthy control (HC) participants using the UPPS-P Impulsive Behavior Scale (UPPS-P). Demographic and clinical correlates and predictors of impulsivity in MUD participants were also investigated. Our findings indicate that the MUD cohort had significantly increased impulsivity ( p < 0.01) compared to the HCs. In the MUD cohort, the UPPS-P total score was also positively correlated with the number of comorbid mental disorders ( r = 0.29, p = 0.04), and degree of family impairment ( r = 0.37, p < 0.01). Multiple linear regression analysis showed that the level of family impairment associated with MUD was significantly associated with impulsivity, explaining 16% of the variance (R 2 = .16, F(2, 51) = 4.88, p = .01). Understanding the clinical correlates and predictors of impulsivity in MUD may inform prevention, early identification, and intervention.